Epidemiological profile of diabetes mellitus in northeastern Brazil (Research, Society and Development, 2019)
The purpose of this article is to present the results of a research that seeks to verify the epidemiology of Diabetes Mellitus in the Northeast region of Brazil. Descriptive and retrospective epidemiological study of a quantitative approach. Secondary data were used through the Hypertensive and Diabetic Registration and Monitoring System (HIPERDIA), made available by DATASUS. The epidemiology of Diabetes Mellitus in the Northeastern region of Brazil was analyzed in the year 2012. There were 9,305 cases, with type II diabetes predominating 72,90%. The state of Bahia presented the highest number of cases for both pathological forms 31.50% and the lowest number in Sergipe 2.80%. There was a greater percentage of females in both type I 59.45% and type II 61.40%. There was a predominance of cases in the age range of 40-59 years. There was a higher prevalence of sedentary lifestyle in relation to smoking and overweight. Among the complications analyzed, diabetic foot, stroke and renal disease were more incidental.